2019
DOI: 10.22146/jtbb.40645
|View full text |Cite
|
Sign up to set email alerts
|

Rotan Potensial dari Hutan Bukit Lubuk Pekak, Merangin, Jambi

Abstract: Rattan is a potential non-timber forest product. It grows in almost all parts of Indonesia, and has been widely used and traded. Indonesia as the largest rattan producer in the world supplies about 85% of world rattan needs. Bukit Lubuk Pekak Forest is part of the Production Forest Management Unit (KPHP) area, Merangin District, Jambi Province. The threat form rattan exploitation is increasing, especially in the Bukit Lubuk Pekak. Therefore, it is necessary to conduct study on the potency of rattan in that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The structure of the rattan species can generally be distinguished from the midrib of leaves, flowers, and fruit (Kalima & Rustiami, 2018). The number of species found on this location was higher compared to the exploration result from Bukit Lubuk Pekak Forest, Merangin, Jambi, where the rattan species were found less than ten species (Kalima et al, 2019). It showed that BTPF has more potencies of rattan to substitute the use of current commercial rattan.…”
Section: A the Population Of Rattan Speciesmentioning
confidence: 75%
See 4 more Smart Citations
“…The structure of the rattan species can generally be distinguished from the midrib of leaves, flowers, and fruit (Kalima & Rustiami, 2018). The number of species found on this location was higher compared to the exploration result from Bukit Lubuk Pekak Forest, Merangin, Jambi, where the rattan species were found less than ten species (Kalima et al, 2019). It showed that BTPF has more potencies of rattan to substitute the use of current commercial rattan.…”
Section: A the Population Of Rattan Speciesmentioning
confidence: 75%
“…Bukit Tiban, Sekupang is the only protected forest in Batam Island (Yuliastrin, 2014), and this result was high enough for rattan population in a protected area compared to the other observations from Andayani et al (2018) that only found seven rattan species in Mandanau Island, Belitung. Another result from Kalima et al (2019) found nine species of rattan in Bukit Lubuk Pekak forest, Merangin, Jambi. The high density of rattan species in Bukit Tiban, Sekupang need to be monitored since the disturbances or the threats to this forest were also high, such as forest fire in a dry season and illegal land conversion.…”
Section: The Density Of Rattan Speciesmentioning
confidence: 99%
See 3 more Smart Citations